PENERAPAN MODEL ARCS (ATTENTION, RELEVANCE, CONFIDENCE, SATISFACTION) BERBANTUAN PREZI TERHADAP KEMAMPUAN BERPIKIR REFLEKTIF SISWA DITINJAU DARI GENDER - Ariyanti, Firly; Sri Anggoro , Bambang; Fadila, Abi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of implementing the Attention, Relevance, Confidence, and Satisfaction (ARCS) learning model assisted by the Prezi application on students’ reflective thinking ability in terms of gender. This research employed a quantitative approach with a quasi-experimental design involving two classes at the senior high school level. One class received instruction using the ARCS learning model assisted by Prezi, while the other class was taught using the Discovery Learning model. Data on students’ reflective thinking ability were collected through an essay test that met the criteria of validity and reliability. The data were analyzed using a two-way ANOVA. The results indicated that students who participated in learning through the ARCS model assisted by Prezi demonstrated better reflective thinking ability than those who learned through Discovery Learning. In addition, there were differences in students’ reflective thinking ability based on gender, as well as an interaction between the learning model and gender on students’ reflective thinking ability. These findings indicate that the effectiveness of learning is influenced by both the learning model and students’ characteristics. Therefore, the ARCS learning model assisted by Prezi contributes positively to improving students’ reflective thinking ability and can be considered an alternative approach in mathematics learning to foster higher-order thinking skills.